Description of two new species of Plesiopelma (Araneae, Theraphosidae, Theraphosinae) from Argentina - Ferretti, Nelson Edgardo (2013)
Two new species of Plesiopelma Pocock, 1901 from northern Argentina are described and diagnosed based on males and habitat descriptions are presented. Males of Plesiopelma paganoi sp. nov. differ from most of species by the absence of spiniform setae on the retrolateral face of cymbium, aspect of the palpal bulb. Plesiopelma aspidosperma sp. nov. differs from most species of the genus by the presence of spiniform setae on the retrolateral face of cymbium and it can be distinguished from P. myodes Pocock, 1901, P. longisternale (Schiapelli & Gerschman, 1942) and P. rectimanum (Mello-Leitão, 1923) by the separated palpal bulb keels and basal nodule of metatarsus I very developed. It differs from P. minense (Mello-Leitão, 1943) by the shape of the palpal bulb and basal nodule on metatarsus I well developed. Specimens were captured in Salta province, Argentina, inhabiting high cloud forests of Yungas eco-region.